2021
DOI: 10.1098/rstb.2020.0313
|View full text |Cite
|
Sign up to set email alerts
|

When does cultural evolution become cumulative culture? A case study of humpback whale song

Abstract: Culture presents a second inheritance system by which innovations can be transmitted between generations and among individuals. Some vocal behaviours present compelling examples of cultural evolution. Where modifications accumulate over time, such a process can become cumulative cultural evolution. The existence of cumulative cultural evolution in non-human animals is controversial. When physical products of such a process do not exist, modifications may not be clearly visible over time. Here, we investigate w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 92 publications
0
22
0
Order By: Relevance
“…Recognizing this, but going far beyond it, articles in this issue address the significance of cases where collective knowledge exists only at the level of the collective, and not in any one individual. The partial or variant knowledge of different individuals that this implies may be distributed across a population in space, and/or over time, with subsequent combinations thence leading to innovations that can drive CCE [ 82 , 93 , 153 155 , 159 , 160 ]. Studies are progressively revealing that how these effects play out may be shaped by numerous interacting factors including the form of social structures and networks [ 93 , 159 , 160 ], relationships between individuals such as in degree of tolerance [ 153 ] or coordination [ 157 ], adaptive biases in model selection such as conformity [ 153 , 163 ], and the socio-cognitive capabilities of participant individuals, such as theory of mind [ 29 , 158 ] and inventiveness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recognizing this, but going far beyond it, articles in this issue address the significance of cases where collective knowledge exists only at the level of the collective, and not in any one individual. The partial or variant knowledge of different individuals that this implies may be distributed across a population in space, and/or over time, with subsequent combinations thence leading to innovations that can drive CCE [ 82 , 93 , 153 155 , 159 , 160 ]. Studies are progressively revealing that how these effects play out may be shaped by numerous interacting factors including the form of social structures and networks [ 93 , 159 , 160 ], relationships between individuals such as in degree of tolerance [ 153 ] or coordination [ 157 ], adaptive biases in model selection such as conformity [ 153 , 163 ], and the socio-cognitive capabilities of participant individuals, such as theory of mind [ 29 , 158 ] and inventiveness.…”
Section: Discussionmentioning
confidence: 99%
“…All such cases are suggestive of collective contributions of different animals' innovations to cumulative cultural change, across significant time-depths. That of the humpback whales is pursued in greater depth in this issue [ 82 ].…”
Section: Collective Behaviour Knowledge and Culture Among Non-human Animalsmentioning
confidence: 99%
“…It has been shown that culture can relax or increase selection pressures and favour adaptations in various species [ 140 , 141 ]. However, the reasons for the transition from a facultative inheritance system to dependence on a system of gene-culture coevolution in hominins remain a puzzle.…”
Section: Discussion: Gene-culture Coevolution and Human Evolutionmentioning
confidence: 99%
“…While the burgeoning research on social learning across the species points at cultural evolution and collective knowledge (see Garland et al . [ 62 ]; Gruber et al . [ 63 ]; Whiten et al [ 64 ]; Wild et al .…”
Section: Navigating Social and Non-social Topologies: Common Mechanisms?mentioning
confidence: 99%